Activation of Secondary Metabolism in Citrus Plants Is Associated to Sensitivity to Combined Drought and High Temperatures - Zandalinas, Sara I.; Sales, Carlos; Beltrán, Joaquim; Gómez-Cadenas, Aurelio; Arbona, Vicent (Frontiers in Plant Science, 2017)
Drought and heat stresses are two of the most frequent environmental factors that take place simultaneously in the field constraining global crop productivity. Metabolism reconfiguration is often behind the adaptation of plants to adverse environmental conditions. Carrizo citrange and Cleopatra mandarin, two citrus genotypes with contrasting ability to tolerate combined heat and drought conditions, showed different metabolite patterns. Increased levels of phenylpropanoid metabolites were observed in Cleopatra in response to stress, including scopolin, a metabolite involved in defense mechanisms. Tolerant Carrizo accumulated sinapic acid and sinapoyl aldehyde, direct precursors of lignins. Finally, Cleopatra showed an accumulation of flavonols and glycosylated and polymethoxylated flavones such as tangeritin. The activation of flavonoid biosynthesis in Cleopatra could be aimed to mitigate the higher oxidative damage observed in this genotype. In general, limonoids were more severely altered in Cleopatra than in Carrizo in response to stress imposition. To conclude, all metabolite changes observed in Cleopatra suggest the activation of energy metabolism along with metabolic pathways leading to the accumulation of photoprotective and antioxidant secondary metabolites, oriented to mitigate the damaging effects of stress. Conversely, the higher ability of Carrizo to retain a high photosynthetic activity and to cope with oxidative stress allowed the maintenance of the metabolic activity and prevented the accumulation of antioxidant metabolites.